THE EFFECT OF PERCEIVED VALUE AND EWOM ON LOYALTY IN THE INDUSTRY CONSUMER GOODS BASED ON EQUITY THEORY - Tasya, Athala Insyira; Marsasi, Endy Gunanto (LPPM STIE Muhammadiah Bandung, 2023)
This study describes the effect of equity theory on perceived value. Equity theory assumes that, generally, a person likes to act with comparability or fairness. The purpose of this research is to understand the perceived value of consumers and the exchange of information carried out by consumers, which can later encourage someone to buy a good or service. The gap in research, namely perceived value, is that previous studies have different results. Based on this explanation, the aim is to see the effect of corporate social responsibility, perceived value, electronic-word-of-mouth, satisfaction, and loyalty on product purchases in the industry consumer goods. In this study, the EWOM variable becomes a novelty. The research object used is the industry consumer goods. The data was distributed using google forms to 276 respondents. Respondents with productive age are 17-64 years old, know social responsibility, and have a domicile in Java. The test utilizes SEM-AMOS 26 and SPSS-26. In using SEM, it wants to provide information to previous researchers. Furthermore, the result is that there is a negative influence on one of the five positive hypotheses. The variable perception of value is rejected, so there is no interest in purchasing consumer goods that cause loyalty.